PENGARUH BEBAN PAJAK TANGGUHAN TERHADAP PERSISTENSI LABA DAN MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR - WIJAYANTI, SRI (Jurnal Akuntansi AKUNESA, 2016)
The purpose of this research is to determine the effect of deferred tax expense to earnings persistence and earnings management. This research use samples from manufacturing companies which listed on Stock Exchange from 2010-2014. The methods of sample collection is by purposive sampling. There are 41 companies with total 205 observations for samples. This research use deferred tax expense as independent variable. The dependent variable consists of the persistence of earnings and earnings management. Earnings persistence is measured by using regression coefficients between accounting profit accounting profit of the current period with last year period, while the profit menajamen measured using income distribution approach. Simple linear regression is used for the variabel test. The results showed that the deferred tax expense don’t have any efffect to perrsistensi income and deferred tax expense also don’t any effect affect to earnings management. It shows that the deferred tax expense can not determine the persistence of earnings and can not detect the presence of earnings management in a company, because the tax burden expense majority increasing because of the differences in financial reporting regulations fiscal and commercial financial statements.